Impact of education based on type 1 diabetes management model - ÇÖVENER ÖZÇELİK, ÇAĞRI (SPRINGER INDIA, 2015)
The diabetes management is considered to be adversely affected when adolescent-specific education methods are not used. In this study, Type 1 Diabetes Management Model which ensures standardisation of the diabetes education and is based on the health promotion model and formed by applying health promotion model (HPM) according to the mastery-learning theory was used. The study was performed to determine effectiveness of diabetes education based on Type 1 Diabetes Management Model on adolescents. In total, 36 adolescents at ages 13-17 with type 1 diabetes participated. A quasi-experimental study was conducted as a pretest-posttest design on a single group study, which included nine interactive type 1 diabetes education sessions over 8 days, with assessments at baseline and after 3 months. Diabetes management skills and self-management levels were measured with Diabetes Behaviour Rating Scale, General Self Efficacy Scale and diabetes knowledge measured with type 1 diabetes rating form and unit follow-up tests. After 3 months, diabetes management skills (p=0.000) and self-management levels (p=0.002) were improved, haemoglobin A1C levels were decreased (p=0.035) and diabetes knowledge was increased (p=0.000). No improvement was observed in levels of taking the responsibility of skills (p=0.958). Education programs based on Type 1 Diabetes Management Model may be suggested as an efficient model for adolescents with type 1 diabetes to improve their diabetes management skills, and also, diabetes nurses will be able to form education programs they arrange within the framework of a specific standard.
Keywords: Adolescent; Diabetes; Diabetes management; Health promotion model; Mastery-learning theory; SELF-MANAGEMENT; ADOLESCENTS; INTERVENTION; OUTCOMES; PROGRAMS; EFFICACY; DISEASE; CHILD; CARE